Efektivitas Media Sosial dalam Meningkatkan Kunjungan ke Perpustakaan Kandaga Unpad - Prijana; Aria Putra, Muhammad Rangga; Fadhil , Fairuz Zulyan; Nur Eka Puri, Mahendra; Bifakhlina, Febriyanti (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This study aims to evaluate the impact of social media utilization as a communication tool in increasing visits by students of the Library and Information Science Study Program at Padjadjaran University to the Kandaga Library, UNPAD. In the midst of the digital era, libraries are required to adapt to establish effective interactions with users. This study explores the role of Kandaga Library's social media in building awareness, attracting interest, and influencing students' decisions to make in-person visits. The research was conducted quantitatively through a survey method with 87 student respondents, with data collected using an online questionnaire and analyzed using the Pearson correlation test. The findings indicate a positive and significant relationship between social media activity and the intensity of library visits. Several elements such as social media content (r=0.628), information clarity (r=0.502), visual and design aspects (r=0.522), and the number of "likes" on posts (r=0.607) showed a significant correlation (p<0.01) with the frequency of visits. These results strengthen the understanding that social media is a powerful communication tool in increasing physical visits to the library, and can be used as a basis for designing more effective communication strategies in the future.